Reflection of Dalit Aesthetics and Consciousness in Prakash Nepali's Andho Samāj - Charmakar, Rudra Bahadur (Patan Pragya, 2023)
This article explores the aesthetic features and values and consciousness in Prakash Nepali's Andho Samāj. The concept of Dalit aesthetics developed in literature includes the various characteristics and issues of Dalits. It embeds many facets of Dalits and their problems connected to caste, culture, economy and society. Nepali’s Andho Samāj elevates diverse problems and complications of Dalits including inter-caste relation, caste system, poverty and cultural practices in the society. In the novel, major Dalit characters try to revolt against the socio-cultural and economic difficulties and barriers through social intermingling and assimilation. They seek the freedom from all forms of restriction, prohibition and difficulties of caste and culture; and, plead for equality, justice and dignity of Dalits. However, the characters such as Hari and Sandhya encounter with suppression, insult and discrimination from the parents, family members and society themselves; and, they are compelled to commit suicide together. Hence, the novel portrays the pain, anger, sufferings and other numerous problems and also resistance, protest and revolt linked to caste, culture, gender and varna system which are considered as aesthetic features and norms of Dalit literature. For that, the researcher applies the concept of Dalit aesthetics and consciousness as theoretical tool and also employs the qualitative approach with explorative methods.